PENGEMBANGAN MODUL BERBASIS MODEL ADIS (ARGUMENT - DRIVENT INQUIRY WITH SCAFFOLDING) PADA MATERI SISTEM REPRODUKSI MANUSIA - Jannah, Nur; Mulyani, HRA; Santoso, Handoko (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
This development research aims to (1) produce a module based on ADIS (Argument-Driven Inquiry with Scaffolding) on material on the human reproductive system class IX in junior high school that is suitable for use. (2) to find out the students' responses to the ADIS-based module (Argument-Driven Inquiry With Scaffolding) on the material of the human reproductive system class IX SMP. This research was conducted at junior high school PGRI 1 Sukadana, East Lampung. This type of research is development research with the development model used by ADDIE, the data collection stage (analysis), the design stage (design), and the development stage (development). the stage of application of teaching materials (implementation), and the stage of feedback (evaluation). The types of data in this study are qualitative and quantitative data. The data collection instruments used in this study were interview sheets, product validation questionnaires, and student response questionnaires. Based on the validation results of module experts it was declared very feasible with a percentage of 85% which was accumulated from an average validation of design experts of 80%, an average validation of material experts of 87%, and validation of linguists 92% with very feasible criteria. Based on the results of the practicality test, the module was stated to be very practical with an average percentage of 91.67%. So it can be concluded that the ADIS (Argument-Driven Inquiry With Scaffolding) based module on the material of the human reproductive system has been declared very feasible and very practical.